Insights into Astrogliosis, Inflammation Processes, and Emerging Treatments by Exosome Therapy and LowLevel Laser Therapy for Spinal Cord Injury: A Systematic Review: Exosome therapy and low-level laser therapy for spinal cord injury - Mosleh, Hamid Reza; Bahrami, Maryam; Tahmasebinia, Foozhan; Abdi, Saeed; Khajavi, Mahdi; Jalali, Mahsa; Tasa, Davood; Abbaszadeh, Hojjat-allah; Keramatinia, Ali Asghar (Journal of Lasers in Medical Sciences, 2025)
Introduction: Spinal cord injury (SCI) is among the most severe medical conditions, with profound impacts on global healthcare systems. SCI results in temporary or permanent loss of spinal cord function and is associated with high incidence rates, substantial economic burden, significant disability, and a low average age of onset. Astrogliosis and neuroinflammation play central roles in secondary injury and limit functional recovery. This systematic review examines pathophysiology, mechanisms of recovery, and emerging clinical treatment strategies for SCI. Methods: A comprehensive literature search was conducted across multiple databases, including PubMed, Scopus, and Web of Science, to identify relevant studies on SCI classification, pathophysiology, and treatment approaches, with a particular focus on Exosome and low level Laser therapy. The search included articles published up to September 2024, and key data were extracted for analysis. Results: A total of 141 studies met the inclusion criteria. The pathogenesis of SCI involves an initial mechanical injury followed by a secondary cascade of molecular and cellular events that exacerbate tissue damage. Current treatment options primarily provide supportive care for patients with lifelong disabilities. Pharmacological interventions focus on neuroprotection, employing medications and therapeutic agents tailored to modulate degenerative processes. Non-pharmacological approaches, including growth factors, Low level laser therapy, cultured cells, and vitamins, offer additional therapeutic benefits. Laser therapy integration into SCI treatment is increasingly studied due to its anti‑inflammatory, neuroprotective, and analgesic effects. Exosome therapies have shown significant neuroprotective and neuroregenerative potential by addressing multiple pathological mechanisms in SCI. Conclusion: A promising future direction lies in combining conventional pharmacological and surgical strategies with emerging therapies, particularly exosome therapy and LLLT, offers a promising approach to mitigate secondary injury, modulate astrogliosis, and enhance recovery in SCI patients. Comprehensive therapeutic strategies integrating pharmacological and nonpharmacological approaches with cutting-edge cell therapies hold significant promise for improving outcomes in SCI treatment.